Effective and emerging treatments in pediatric psychology - Spirito, Anthony (Oxford University Press, 2006)
This volume provides practicing clinicians and researchers with an update on treatments found to be effective in pediatric psychology, as well as those that are emerging in the field and have promise of being proven effective as additional research is conducted. Several chapters contain descriptions of different treatment protocols as well as specific scripts for certain procedures. These materials will be useful to clinicians in their day-to-day practice and clinical researchers in implementing and/or developing research protocols. Leading pediatric psychology intervention researchers generously provide details of their treatments for a number of pediatric problems. This book provides a means by which treatment manuals and related data on the outcomes of interventions can be disseminated to practicing pediatric psychologists and to investigators. Readers can gain access to treatment protocols developed by leading pediatric psychology researchers at a website specifically developed for this book. Readers may use these manuals in clinical work or contact the manual developers if interested in using/adapting the manuals for research protocols.; This website will be updated with additional treatment manuals for problems encountered in the practice of pediatric psychology.